2017
DOI: 10.1186/s12882-017-0707-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations of genetic variants of endothelin with cardiovascular complications in patients with renal failure

Abstract: BackgroundCardiovascular (CV) complications are the main cause of death in end-stage renal disease (ESRD) patients. The high CV risks are attributable to the additive effects of multiple factors. Endothelin (EDN) is a potent vasoconstrictor and plays a role in regulating vascular homeostasis. However, whether variants of the EDN gene are associated with risks of CV events is not known. We conducted a study to investigate associations of variants of the EDN gene with CV events in ESRD patients.MethodsA cohort o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Also, ET-1 has been shown to stimulate ROS production [9] and correlate with the risk of inflammatory diseases such as atherosclerosis. Our previous study showed genetic variants of EDN1 gene are associated with an increased risk of hospitalization for a cardiovascular event [31]. Pittet et al demonstrated that the serum level of ET-1 was strongly correlated with reduced cardiac output in sepsis patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…Also, ET-1 has been shown to stimulate ROS production [9] and correlate with the risk of inflammatory diseases such as atherosclerosis. Our previous study showed genetic variants of EDN1 gene are associated with an increased risk of hospitalization for a cardiovascular event [31]. Pittet et al demonstrated that the serum level of ET-1 was strongly correlated with reduced cardiac output in sepsis patients [32].…”
Section: Discussionmentioning
confidence: 99%